New molecular targets in non clear renal cell carcinoma: An overview of ongoing clinical trials. Issue 7 (July 2015) - Ciccarese, Chiara; Massari, Francesco; Santoni, Matteo; Heng, Daniel Y.C.; Sotte, Valeria; Brunelli, Matteo; Conti, Alessandro; Cheng, Liang; Lopez-Beltran, Antonio; Scarpelli, Marina; Cascinu, Stefano; Tortora, Giampaolo; et al.
Abstract : Highlights: nccRCC subtypes differ for their biological and clinical behavior. VEGF/VEGFR, mTOR and MET signaling pathways play a prominent role in nccRCC. The efficacy of anti PD-1/PDL-1 approaches should be tested in nccRCC patients. Understanding the molecular landscape of nccRCC is crucial for future therapies. Abstract: Non-clear cell renal cell carcinomas (nccRCCs) are a heterogeneous group of tumors, characterized by different histological features, molecular alterations, clinical outcomes, and responses to treatment. According to the 2004 WHO classification, 50 different histotypes were recognized. In 2013, five new distinct epithelial tumors and three provisional entities have been added to this classification, relying on morphology, immunohistochemistry, cytogenetics, and molecular pathology advances. Targeted therapies against VEGF and mTOR pathways have become the cornerstones of the treatment for clear cell RCC, dramatically revolutionizing the patients' prognosis. Interestingly, other than mTOR and VEGF pathways, tumor proliferation of some nccRCC histotypes seems to depend on alternative signaling pathways, as demonstrated by the close correlation between papillary RCC and activation of the HGF/MET axis. Currently, several strategies are under evaluation in patients with nccRCC. These approaches include TKIs and mTOR inhibitors, MET-pathway antagonists and immunotherapy. The aim of this review is to analyze the rationale for the use of TKIs and mTOR inhibitors as treatment options for nccRCC and to describe the future therapeutic perspectives for these patients.